Hassuna Pottery - Dabbagh, Takey
Taqī ad-Dabbāġ; Tali Ḥassūna; publ. 1967; on pl. I-IX = pp. 103-111; pottery from the following sites: Tell Hassuna, Tell Arpachiyah, Nineveh, Samarra, Ali Agha, El-Khan, Jarmo, Mattara, Shimshara, Yarmin Tepe, Ibrah Kahir, Kidri Baskin, Mesejra, Nakkar, Rebedha, Ibrahim Bayis, Amuq, Baghouz, Tell Chaghar Bazar, Mersin, Tarsus, Sakçgözü.